2007
DOI: 10.1007/s10692-007-0032-9
|View full text |Cite
|
Sign up to set email alerts
|

Lyocell fibres based on direct dissolution of cellulose in N-methylmorpholine N-oxide: Development and prospects

Abstract: The scientific principles of direct dissolution of cellulose in the NMMOwater system demonstrate the major possibility of obtaining concentrated spinning solutions and spinning hydrated cellulose fibres from them. The specific features of the properties of NMMO (high boiling point and insufficient thermal stability) that dissolves the NMMOwater system (narrow concentration range, optimum for dissolution of cellulose) makes it necessary to recycle the washing water by evaporating it, which causes high power con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 9 publications
(9 reference statements)
1
64
0
Order By: Relevance
“…Commercially, Lyocell fibers are regenerated cellulose fibers spun from a cellulose solution in a mixture of N-methylmorpholine N-oxide (NMMO) and water. This process is used to manufacture fibers for the textile industry (Perepelkin 2007). The Lyocell process has some drawbacks linked to the instability of the solution in presence of certain metals and of the tendency of the fibers to fibrillate in wet state.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially, Lyocell fibers are regenerated cellulose fibers spun from a cellulose solution in a mixture of N-methylmorpholine N-oxide (NMMO) and water. This process is used to manufacture fibers for the textile industry (Perepelkin 2007). The Lyocell process has some drawbacks linked to the instability of the solution in presence of certain metals and of the tendency of the fibers to fibrillate in wet state.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the possibility of nearly complete recycling of the solvent in the NMO-based processes, NMO is non-toxic and fully biodegradable (Rosenau et al, 2003). Furthermore, the process works under moderate conditions which are ambient pressure and a temperature between 90 and 1208C (Perepelkin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These results are comparable with the results of the commercial lyocell fiber used in our study (tensile strength 486 MPa and initial modulus 16 GPa), and the results reported in related literature (tensile strength 525 $ 600 MPa, and initial modulus 8 $ 18 GPa). 35,36 CONCLUSIONS Sugarcane bagasse was dissolved in NMMO 0.9 hydrate, and fibers were prepared by dry jet-wet spinning in aqueous NMMO solutions. We evaluated different NMMO concentrations from 0 to 50% in aqueous coagulating baths.…”
Section: Characteristics Of Fibers After Nmmo Removalmentioning
confidence: 99%